A Serosurvey for Ruminant Pestivirus Exposure Conducted Using Sera From Stray Mexico Origin Cattle Captured Crossing Into Southern Texas - Falkenberg, Shollie M.; Bauermann, Fernando V.; Scoles, Glen A.; Bonilla, Denise; Dassanayake, Rohana P. (Frontiers in Veterinary Science, 2022)
U.S. Department of Agriculture (USDA), Animal Plant Health Inspection Service (APHIS), Cattle Fever Tick Eradication Program (CFTEP) monitor a quarantine zone along the Texas border to prevent the introduction of stray livestock carrying cattle fever ticks entering the U.S. from Mexico. Stray cattle collected by CFTEP are checked for ticks and several infectious disease-causing pathogens, but not for bovine viral diarrhea virus (BVDV). BVDV is one of the most economically impactful viruses affecting U.S. cattle producers. BVDV is present in all parts of the world, but it has been demonstrated that another distantly related pestivirus, HoBi-like pestivirus (HoBiPev), can also cause BVD. To date HoBiPev has not been detected in the United States, but commonly found in Brazil, and sporadically in Europe, and Asia. The objective of the current study was to evaluate the seroprevalence of pestiviruses, with a specific focus on HoBiPev, in stray cattle. Virus neutralization (VN) assay was used to determine seroprevalence (or antibody titers) of BVDV-1, BVDV-2, and HoBiPev. Approximately 50% (67 of 134) samples were seropositive for pestiviruses, all 67 positive samples were positive (50%) for BVDV-1, 66 samples of the 67 were positive (49.3%) for BVDV-2 and the same 66 samples of the 67 were also positive (49.3%) for HoBiPev. Due to the antigenic cross-reactivity among Pestiviruses, the comparative antibody against each pestivirus was calculated from all VN-positive samples. Titers were clearly higher against BVDV-1, and only one sample had a titer clearly higher against BVDV-2. No sample had an antibody titer higher for HoBiPev, and while this does not prove the absence of HoBiPev, it does provide evidence that the prevalence of HoBiPev is less predominant than BVDV-1. Additionally, data from these samples provide evidence on the susceptibility of animals that may enter into the US, with approximately 50% of the animals were seronegative for bovine pestiviruses. This cattle population provides a unique opportunity to evaluate and monitor changes in seroprevalence of economically important cattle diseases affecting the cattle industry.